Where Have Eye Been? Observers Can Recognise Their Own Fixations. (October 2013) - Foulsham, Tom; Kingstone, Alan
We are often not explicitly aware of the location of our spatial attention, despite its influence on our perception and cognition. During a picture memory task, we asked whether people could later recognise their eye fixations in a two-alternative test. In three separate experiments, participants performed above chance when discriminating their own fixation patterns from random locations or locations fixated in a different image. Recognition was much poorer when the task was to spot your own versus someone else's fixations on the same stimulus, but performance remained better than chance. That we are sensitive to our own scan patterns has implications for perception, memory, and meta-cognition.